2019
DOI: 10.1002/anie.201912111
|View full text |Cite
|
Sign up to set email alerts
|

Water Purification and Microplastics Removal Using Magnetic Polyoxometalate‐Supported Ionic Liquid Phases (magPOM‐SILPs)

Abstract: Filtration is an established water-purification technology.H owever,d ue to lowf low rates,t he filtration of large volumes of water is often not practical. Herein, we report an alternative purification approach in whichamagnetic nanoparticle composite is used to remove organic, inorganic, microbial, and microplastics pollutants from water.T he composite is based on ap olyoxometalate ionic liquid (POM-IL) adsorbed onto magnetic microporous core-shell Fe 2 O 3 / SiO 2 particles,g iving am agnetic POM-supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(83 citation statements)
references
References 34 publications
1
82
0
Order By: Relevance
“…Ionic liquids (ILs) are salts with a melting point <100 • C, whose structure can be tuned to access physicochemical properties such as wide electrochemical window, high thermal stability and null vapour pressure [21][22][23]. Importantly, unique properties of POM-ILs have been harnessed for universal pollutant removal [24] and reactive surface protecting anti-corrosion coatings [25][26][27] because both the anion and cation can be tailored to target biological, organic and inorganic pollutants including microbes, acids and reactive oxygen species [28]. Their rheological properties and hydrophobicity can also be tuned by chemical design, which are important to obtain surface coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) are salts with a melting point <100 • C, whose structure can be tuned to access physicochemical properties such as wide electrochemical window, high thermal stability and null vapour pressure [21][22][23]. Importantly, unique properties of POM-ILs have been harnessed for universal pollutant removal [24] and reactive surface protecting anti-corrosion coatings [25][26][27] because both the anion and cation can be tailored to target biological, organic and inorganic pollutants including microbes, acids and reactive oxygen species [28]. Their rheological properties and hydrophobicity can also be tuned by chemical design, which are important to obtain surface coatings.…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates that this sampling device is suitable to capture a wide range of particle sizes. Unlike the previous methods, Misra et al (2019) developed a novel procedure using ionic liquids [55]. This approach is based on nanoparticles with a core of magnetic iron oxide and a shell of porous silicon dioxide.…”
Section: Removal Of Microplastics: From Laboratory To Large Scalementioning
confidence: 99%
“…The same research group reported the magnetically separable adsorbent comprising of lacunary POM adsorbed on the magnetite-silica composite. [11] Recently, poly(ionic liquids)-POM hybrid was prepared by ionic self assembly process. [12] The selective adsorption of dyes can be regulated by changing the proportion of poly ionic liquids and [Mo 8 O 26] 4À .…”
Section: Introductionmentioning
confidence: 99%